Implementasi Peraturan Bupati Tentang Tata Cara Pemungutan Pajak Hotel Dan Pajak Restoran Di Atas Kapal Wisata Dalam Meningkatkan Kepatuhan Wajib Pajak Di Kabupaten Manggarai Barat Tahun 2021 - Eva Alfari Bugis; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2022)
Hotel and restaurant taxes on tourist boats have not yet reachedthe target set by the local government of West Manggarai Regency. This phenomenon shows that the level of taxpayer compliance is still very low. Therefore, it is necessary to carry out proper implementation of the West Manggarai Regent's Regulation Number 58 of 2017 concerning Procedures for Collecting Hotel and Restaurant Taxes on Tourist Boats. This study aimed to analyze the implementation of the Regent's Regulation on Procedures for Collecting Hotel and Restaurant Taxes on Tourist Boats in an effort to improve taxpayer compliance as well as to analyze the obstacles faced and the efforts taken by the Regional Revenue Agency to overcome these obstacles. The research methodused was qualitative with a descriptive research type. The results of the study indicate that the Regent's Regulation on Procedures for Collecting Hotel and Restaurant Taxes on Tourist Boats has not been implemented properly due to the lack of socialization, inadequate human resource capabilities, insufficient infrastructure support, low supervision, and unidealimplementation of Standard Operating Procedures (SOP). Therefore, it is necessary to increase socialization, supervision, firm legal efforts, as well as education and training activities for Human Resources.